2023
DOI: 10.5114/aoms/159313
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoids in human heart failure: pilot study of plasma epoxyeicosatrienoic and dihydroxyeicosatrienoic acid levels

Abstract: IntroductionThe role of eicosanoids, metabolites of arachidonic acid with cardio-renal activity, remains unclear in human heart failure (HF).Material and methodsWe enrolled 50 patients with HF to measure plasma 14,15-EET and 14,15-DHET levels using commercial ELISA kits and compared them with 25 age- and sex-matched controls.ResultsBoth of the measured eicosanoids were significantly higher in the HF group: 14,15-EET (91.3 ±25.7 ng/ml vs. 64.95 ±35.4 ng/ml) and 14,15-DHET (10.58 ±2.06 ng/ml vs. 9.07 ±1.60 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…CYP-derived EETs represent a promising therapeutic strategy for cardiac remodeling and dysfunction. At baseline, a pilot study of patients with acute decompensated HFrEF showed increased plasma 14,15-EET levels [ 56 ]. Cardiac CYP2J2 overexpression significantly attenuates Angiotensin II (Ang II)-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…CYP-derived EETs represent a promising therapeutic strategy for cardiac remodeling and dysfunction. At baseline, a pilot study of patients with acute decompensated HFrEF showed increased plasma 14,15-EET levels [ 56 ]. Cardiac CYP2J2 overexpression significantly attenuates Angiotensin II (Ang II)-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%